Cervicogenic Headache and the Neck Ability to Perform Activities of Daily Livings Associated to Mobile Phone Usage - Anam Shahzadi, Aniqa Tabasum, Sara Gul, Muhammad Hussain Iqbal, Zahid Hussain, Farida Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Cervicogenic headache is a secondary headache, which means that it is caused by another illness or physical issue. In case of cervicogenic headache, the cause is a disorder of cervical spine and its soft tissue elements disc. Aim: To determine the cervicogenic headache and the neck ability to perform activities of daily livings associated to mobile phone usage. Methodology: This descriptive study was done among 355 participants from different institutes i.e. colleges and universities. This study was executed to find the cervicogenic headache and its impact on neck ability in ADLs. All ethical issues were computed and an informed consent was taken from the administration of concerned institutes and from individuals who were willing to participate. Results: Among 355 participants who feel neck pain were 266(74.93%) and participants do not feel neck pain were 89(25.07%). 87(24.51%) spend 1-2 hour ,87(24.51%) spend 2-3 hour time daily on mobile phone, 91(25.63%) spend 3-4 hour time daily on mobile phone, 88(24.79%) spend more than 5 hour time daily on mobile phone. Pain Intensity according to Visual Analogue Scale was mild among 51(14.37%), Moderate among 265(74.65%) and Severe among 39(10.99%). Conclusion: Frequency of cervicogenic headache was high due to mobile phone use in young adults. Cervicogenic headache is associated with poor neck posture, poor neck alignment, limited range of motion of cervical spine. There was significant association between time spend daily on mobile phone and cervicogenic headache. Keywords: Cervicogenic Headache, Mobile, Headache,